ANALISIS KESALAHAN SISWA DALAM MEMECAHKAN MASALAH FISIKA BERDASARKAN POLYA PADA POKOK BAHASAN FLUIDA STATIS DI SMAN JEMBER - Lailiatur Rohmah; Sri Handono B,P; Yushardi Yushardi (JURNAL PEMBELAJARAN FISIKA, 2018)
This research was analyzed the mistake of high school student in solving physics problem on matter of static fluid based on Polya, therefore this research was included in descriptive research. The purpose of this research was describe the level of student’s mistake in solving problems on matter of static fluid based on Polya and its causes. Respondents in this research were 98 students from SMAN A, SMAN B, and SMAN C, each taken one class from each school. The instrument used in this research was a test question that consists of 5 questions and interviews. The results of the research from the three schools indicated that students often make mistakes in completing the plan, then the second most common mistake was a mistakes in checking again, while the third mistake was a mistakes in making the plan, and the mistake that the students rarely made mistakes in understanding question.Key word: Analyzed of Mistake, Problem Solving based on Polya, Static Fluid